RENCANA PENGELOLAAN LANSKAP ZONA PIKNIK KELUARGA TAMAN WISATA ALAM GUNUNG TUJUH, TAMAN NASIONAL KERINCI SEBLAT - Mohammad Isrok Nugroho; Rijanto Djoko (Universitas Tribhuwana Tunggadewi, 2007)
Recreation Park or natural recreation site is the reserved area for natural conservation zone, which has the function for education, science, research, culture, especially for recreation and tourism. Site management of natural recreation park inside the Kerinci Seblat National Park generally has not well been managed, because TNKS does not have enough professional human resource to maintain and to manage the recreational area. The plan of landscape management for family picnic zone of Gunung Tujuh Natural Park, Kerinci Seblat National Park describe by spatial for each of zone that has already developed in the site. The plan of landscape management in this zone was decided by carrying capacity of this site and by the facilities. The goals of landscape management plan were to obtain the function of family picnic zone and establish management program for the sustainability of preserved area of Kerinci Seblat National Park